2017
DOI: 10.7860/jcdr/2017/21703.9467
|View full text |Cite
|
Sign up to set email alerts
|

Herbs in Oral Mucositis

Abstract: Search strategy: Electronic searches through PubMed, MEDLINE, Cochrane Database, and Google Scholar were accomplished and a reference list of relevant articles was undertaken. Among them English-language papers with available full texts focusing on the medicinal herbs in the treatment of cancer therapy-induced oral mucositis were chosen. The keywords used were medicinal plant, chemotherapy, oral ulcer, mouth ulcer, oral mucositis, stomatitis, radiotherapy, and neoplasms.Aloe vera: The Aloe vera plant includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
1
28
0
3
Order By: Relevance
“…Other biomaterials or herbal products, such as Aloe vera, Acacia catechu, Chamomile, Hangeshashinto, indigowood root (Isatis indigotica Fort. ), honey, Traumeel S, water grass decoction, and Weleda Ratanhia, also showed similar effects on the alleviation of OM via anti-inflammation activities [17,[63][64][65][66][67][68][69][70][71][72]. The bioactive properties of the yarrow plant (Achillea mileofolium), honey, Callendula officinalis flowers, Hipophae rhamnoides L. plant, Chamomile, and Aloe vera were associated with antioxidant, anti-inflammatory, antibacterial, and wound healing effects of oral mucositis therapy (Table 4) [64][65][66][72][73][74][75][76][77].…”
Section: Potential Use Of C Osmophloeum For the Treatment Of Oral Mumentioning
confidence: 79%
“…Other biomaterials or herbal products, such as Aloe vera, Acacia catechu, Chamomile, Hangeshashinto, indigowood root (Isatis indigotica Fort. ), honey, Traumeel S, water grass decoction, and Weleda Ratanhia, also showed similar effects on the alleviation of OM via anti-inflammation activities [17,[63][64][65][66][67][68][69][70][71][72]. The bioactive properties of the yarrow plant (Achillea mileofolium), honey, Callendula officinalis flowers, Hipophae rhamnoides L. plant, Chamomile, and Aloe vera were associated with antioxidant, anti-inflammatory, antibacterial, and wound healing effects of oral mucositis therapy (Table 4) [64][65][66][72][73][74][75][76][77].…”
Section: Potential Use Of C Osmophloeum For the Treatment Of Oral Mumentioning
confidence: 79%
“…Several therapeutic approaches have been employed to date to prevent and treat OM lesions (Lalla et al, ). However, efforts remain focused on the continuing search for new therapies for mucositis (Baharvand et al, ; Dos Santos Filho et al, ). Herbal products have attracted significant attention of researchers in this field (Koohi‐Hosseinabadi et al, ; Koohi‐Hosseinabadi et al, ; Mardani et al, ; Showraki et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other anti‐inflammatory agents have also been studied in the management of OM (Barbosa et al, ). Herbal medicines have been considered as new modalities to be studied for the management of inflammatory conditions, including mucositis (Baharvand, Jafari, & Mortazavi, ; Cinausero et al, ), because they are safe, easily accessible, and inexpensive. Among several phytotherapeutic agents, our study group previously showed that chamomilla is effective in the treatment of OM in a hamster model reducing the tissue levels of interleukin 1 beta and tumor necrosis factor alpha (TNF‐α; Curra et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, mistletoe extracts may alleviate cancer-related fatigue [212]; preparations from the holy basil Ocimum sanctum L. (Lamiaceae) may avert radiation-induced clastogenesis [213]; those based on A. vera may prevent or treat radiation-induced oral mucositis [214]; and the gingerols and shogaols in Z. officinale may reduce the cardiotoxicity of doxorubicin [215]. These compounds may exercise their protective effects through their anti-inflammatory, immunemodulating, free radical-scavenging, antioxidant, and/or metal-chelating properties [212][213][214][215].…”
Section: Discussionmentioning
confidence: 99%